Indeks Topologi Berbasis Simpul dari Graf Koprima Prima untuk Grup Bilangan Bulat Modulo - Romdhini, Mamika Ujianita; Maulana, Fariz; Satriyantara, Rio; Alfian, Muhammad Rijal; Abdurahim, Abdurahim (Jurnal Matematika; Vol 15 No 1 (2025)DO - 10.24843/JMAT.2025.v15.i01.p186, 2025)
The coprime prime graph of the integers modulo group is a graph where the vertices consist of all members of the group. An edge in the coprime prime graph is formed between two vertices whose greatest common divisor (GCD, or FPB in bahasa) of the orders of the two elements is either one or a prime number. This article derives the general formulas for the Atom Bond Connectivity, Forgotten, and Sombor polynomials Index.